Evaluation of mental health of dental students in Mashhad School of Dentistry by SCL-90 questionnaire, 2020-2021 - Neda Eslami; Farzaneh Lal Alizadeh; Samira Mohammadzadeh; Mohammad Sadegh Nazari (Mashhad University of Medical Sciences, 2023)
Background: Considering the mental health of dental students is highly important due to its impact on the physical and mental health of the patients they treat. This study aimed to investigate the mental health of undergraduate dental students of Mashhad Dental School, in the academic year of 2020-2021.Methods & Materials: In this descriptive-analytical cross-sectional study, the 90-item SCL-90-R questionnaire was distributed among undergraduate dentistry students of Mashhad University of Medical Sciences, Mashhad, Iran. Data were collected through both online and paper-based surveys from September 2020 - June 2021. The mental health status of each participant was determined according to the obtained score and was classified as one of the four categories: no mental disorder (0-1), mild mental disorder (1-2), moderate mental disorder (2-3), and severe mental disorder (3-4). The collected data were analyzed in SPSS software (version 20) using Mann-Whitney and Kruskal-Wallis tests.Results: This study was conducted on 530 dental students, among whom 52.6% (n=279) and 47.4% (n=251) of the subjects were female and male, respectively. Based on the results, 26% (n=138), 3.8% (n=20), and 0.4% (n=2) of the participants had mild, moderate, and severe disorders, respectively. The worst mental health statuses were related to the fields of paranoid ideation, obsession-compulsion disorders, and interpersonal sensitivity, while the best mental health status was found in the field of phobic anxiety. According to the findings, the only significant relationship was found between mental health and gender (P=0.012). No significant relationships were observed between mental health status and marital status (P=0.283), residential status (P=0.728), semester of entry (P=0.222), and year of entry (P=0.964).Conclusion: Based on the results, the majority of the students lacked mental disorders and about one-third of the students suffered from mental disorders. Female students had significantly worse mental health status compared to males. There was no statistically significant relationship between other variables and mental health.Keywords: Dental students, mental health, SCL-90-R questionnaire